Regulating the revolving door of regulators - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2023)
This paper analyzes the effects of the revolving door, focusing not only on the relationship between regulators and firms, but analyzing whether regulating the revolving door is optimal from the point of view of society. This paper examines the tradeoff between these two elements linked to the revolving door: 'lack of competence' and 'greed'. On the one hand, the revolving door enables government to hire regulators which are highly qualified individuals due to their prospect of a high future compensation package. On the other hand, the revolving door enables regulators to be greedy, and receive revenues after their term in office. There are two distinct motivations for being greedy: 'regulatory capture', which is unlawful, and 'abuse of power', which is legal, although unethical. This paper highlights that distinguishing whether a behavior is unlawful or unethical is of utmost importance for analyzing the optimal policy concerning regulators. Models of capture require that the revolving door should be regulated to prevent corruption, while models of abuse of power, in which regulators create 'bureaucratic capital', lead to allowing the revolving door practice.
Keywords: H10; H70; O11; O43; 330; bureaucratic capital; compensation package; corruption; ethics; legal system; revolving door; social norms